The Effectiveness Of Iron Tablets, Date Juice, And Honey On Increasing Hemoglobin Levels In Anemic Adolescents At Mts Raudhatul Ulum Sakatiga In 2025 - Abela Mayunita; Riski Riski (Universitas Pahlawan Tuanku Tambusai, 2025)
To determine the effectiveness of administering a combination of Fe tablets, date juice, and honey in increasing hemoglobin levels in female adolescents with anemia at MTs Raudhatul Ulum Sakatiga in 2025. This study used a quasi-experimental design with a pretest-posttest approach without a control group. A sample of 14 anemic female adolescents was selected using a total sampling technique. The intervention was given in the form of a combination of Fe tablets, date juice (250 ml), and honey (15 ml) every day for 4 days. Hemoglobin levels were measured before and after the intervention using a digital Hb device. Data were analyzed using a paired t-test to determine significant changes in hemoglobin levels. The results showed an increase in hemoglobin levels in adolescent girls after intervention with a combination of Fe tablets, date juice, and honey. The average increase in hemoglobin levels was ≥ 1 g/dL with a significance value of p < 0.05, indicating that the intervention was effective. Most respondents experienced an increase from mild anemia to normal, and showed increased energy and enthusiasm for learning. The combination of iron tablets, date juice, and honey has been shown to be effective in increasing hemoglobin levels in adolescent girls with anemia. This intervention also improves compliance due to its preferred taste. Schools, community health centers, and families are recommended to consider this combination therapy as a more natural and acceptable alternative treatment for anemia among adolescents.